IMPORTANCE OF VOCABULARY IN TEACHING FOREIGN LANGUAGES - Shokhista, Obidjonova Bakhtiyorovna; Baratova, Dilafruz (INTERNATIONAL CONFERENCES, 2023)
The article is devoted to the study of the instruction of vocabulary and its importance in teaching foreign languages, especially in English language classrooms.